Development of an eHealth Program for Parents of Adolescents With Type 1 Diabetes. Issue 1 (February 2018) - Whittemore, Robin; Zincavage, Rebekah M.; Jaser, Sarah S.; Grey, Margaret; Coleman, Julia L.; Collett, David; Delvy, Roberta; Basile Ibrahim, Bridget; Marceau, Lisa D.
Purpose: The purpose of this study was to understand the experience of parenting an adolescent with type 1 diabetes (T1DM), to develop a prototype of an eHealth program for parents of adolescents with T1DM, and to evaluate the prototype content and acceptability from the perspective of parents and health care providers. Methods: A multiphase method was used generating both qualitative and quantitative data at multiple time points. There were 27 parents of adolescents aged 12 to 18 years with T1DM and 16 health care providers who participated in semistructured interviews to identify parental challenges; 53 parents and 27 providers evaluated the prototype. Thematic content analysis was used to analyze interview transcripts, and descriptive statistics were used to summarize survey data. Results: Challenges experienced by parents of adolescents with T1DM included understanding the developmental and hormonal changes of adolescence that affect diabetes care, feeling tension between adolescent independence and parent control, communicating without nagging or conflict, transferring diabetes care responsibility safely, dealing with feelings of stress and distress, and perceiving a lack of resources for T1DM care and insufficient personal time for self-care. In the prototype evaluation, both parents and providers found content to be relevant and provided feedback to guide the development of the full program. Conclusions: Parents of adolescents with T1DM and providers expressed a need for parents to have more support in transitioning diabetes care from parent to adolescent. eHealth programs offer an ideal way to address these needs and ultimately can be linked to electronic medical records improving quality and efficiency of health care in this population.